Constitutive modeling of human femoropopliteal artery biaxial stiffening due to aging and diabetes. (December 2017) - Desyatova, Anastasia; MacTaggart, Jason; Kamenskiy, Alexey
Graphical abstract: Abstract: Atherosclerotic obstructive disease of the femoropopliteal artery (Peripheral Arterial Disease, PAD) is notorious for high treatment failure rates. Older age and diabetes mellitus (DM) are among the major risk factors for PAD, and both are associated with increased arterial stiffness. Our goal was to develop a constitutive model describing multiaxial arterial stiffening, and use it to portray aging of normal and diabetic human femoropopliteal arteries (FPA). Fresh human FPAs (n = 744) were obtained from 13–82-year-old donors. Arteries were tested using planar biaxial extension, and their behavior was modeled with a constitutive relation that included stiffening functions of age. FPA diameter, wall thickness, circumferential, and longitudinal opening angles increased with age, while longitudinal pre-stretch decreased. Diameter and circumferential opening angle did not change with age in subjects with DM. Younger FPAs were more compliant longitudinally but became more isotropic with age. Arteries with DM stiffened significantly faster in the circumferential direction than arteries without DM. Constitutive model accurately portrayed orthotropic stiffening with age of both normal and diabetic arteries. Constitutive description of FPA aging contributes to understanding of arterial pathophysiology and can help improve fidelity of computational models investigating device-artery interaction in PAD repair by providing more personalized arterial properties. Statement of Significance: We have analyzed n = 744 human femoropopliteal artery (FPA) specimens using biaxial tensile testing to derive constitutive description of FPA aging in diabetic and non-diabetic subjects. The proposed model allows determination of FPA mechanical properties for subjects of any given age in the range of 13–82 years. These results contribute to understanding of FPA pathophysiology and can help improve fidelity of computational models investigating device-artery interaction in peripheral arterial disease repair by providing more personalized arterial properties. In addition, they can guide the development of new materials tunable to diabetic and non-diabetic arteries.